1993
DOI: 10.1097/00000658-199312000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Diaphragmatic Hernia Occult Marker of Serious Injury

Abstract: The recognition of diaphragmatic rupture is important because of the frequency and severity of associated injuries. The difficulties in reaching the diagnosis require an aggressive search in patients at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
188
2
24

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(218 citation statements)
references
References 13 publications
4
188
2
24
Order By: Relevance
“…Intrathoracic injuries such as pneumohemothoraces and multiple rib fractures are seen in 90% of patients with blunt DI [17,30,31]. Meyers et al [9] reported a 5% incidence of aortic injury in 68 patients with diaphragm rupture at a level I trauma center. Common associated intraabdominal injuries involve the spleen, in 27-60% of cases, and liver in 93% of patients with right and 24% of patients with left-sided diaphragm ruptures [1,7,15,16].…”
Section: Associated Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrathoracic injuries such as pneumohemothoraces and multiple rib fractures are seen in 90% of patients with blunt DI [17,30,31]. Meyers et al [9] reported a 5% incidence of aortic injury in 68 patients with diaphragm rupture at a level I trauma center. Common associated intraabdominal injuries involve the spleen, in 27-60% of cases, and liver in 93% of patients with right and 24% of patients with left-sided diaphragm ruptures [1,7,15,16].…”
Section: Associated Injuriesmentioning
confidence: 99%
“…Common associated intraabdominal injuries involve the spleen, in 27-60% of cases, and liver in 93% of patients with right and 24% of patients with left-sided diaphragm ruptures [1,7,15,16]. Other common concurrent extrathoracic and extraabdominal injuries include pelvic fractures (40-55%), long bone fractures (45-85%), and closed head injury (25-55%) [9,32].…”
Section: Associated Injuriesmentioning
confidence: 99%
“…[3] These patients usually have multi system injuries because of the large force required to rupture the diaphragm. [4] Diaphragm is the musculotendinous structure that seals the inferior thoracic aperture. Diaphragm is not flat, rather it balloons superiorly on both the sides to form domes, the right dome is higher than left, reaching as far as rib V. [5] There are three openings permitting the passage of three large structures.…”
Section: Discussionmentioning
confidence: 99%
“…O reconhecimento da ruptura diafragmática é importante pela frequência e gravidade das lesões associadas 38 .…”
Section: Lesões Associadasunclassified